2019
DOI: 10.3390/w11010154
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Flooding Dynamics and Nutrients’ Controls upon Phytoplankton Functional Dynamics in Amazonian Floodplain Lakes

Abstract: The processes in tropical floodplain lakes enable maintaining phytoplankton nutrient requirements over a hydrological year. The nutrients such as nitrogen, phosphorus and carbon compounds play an essential role in phytoplankton growth. However, the way that nutrients and phytoplankton interact and how this relationship varies seasonally in tropical freshwater ecosystems is not clear. In this study, we evaluate the relationship between phytoplankton–nutrients over the hydrological cycle in Amazonian floodplain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Affonso et al (2011) previously reported an increase in trophic state along the hydrological year for the Curuai floodplain, but their TSI T computation led to higher trophic state than in our study. The increase of the trophic state along the hydrological year was also suggested in Kraus et al (2019) and reflects the successive influence of river incursion and biogeochemical processes in the floodplain along the hydrological year. During the rising period, the river incursion across the floodplain is the major process that brings nutrients and organic matter into the floodplain (Junk et al 1989).…”
Section: Codonsmentioning
confidence: 70%
See 3 more Smart Citations
“…Affonso et al (2011) previously reported an increase in trophic state along the hydrological year for the Curuai floodplain, but their TSI T computation led to higher trophic state than in our study. The increase of the trophic state along the hydrological year was also suggested in Kraus et al (2019) and reflects the successive influence of river incursion and biogeochemical processes in the floodplain along the hydrological year. During the rising period, the river incursion across the floodplain is the major process that brings nutrients and organic matter into the floodplain (Junk et al 1989).…”
Section: Codonsmentioning
confidence: 70%
“…Therefore, despite a smaller TP concentration during the flushing period, the bioavailable P could be higher. But according to Kraus et al (2019), the proportion of bioavailable P (PO 4 ) during the flushing period is even smaller than during the rising period. Our results during this period are therefore more likely explained by the fact that P is not the main limiting factor of phytoplankton growth during this period.…”
Section: Codonsmentioning
confidence: 97%
See 2 more Smart Citations
“…The OACs vary widely and independently from each other, making freshwater optically complex environments [8,9]. The OAC concentration modifies the underwater light field, regulating the water transparency and impacting aquatic organisms such as fishes [10] and phytoplankton [11][12][13].…”
Section: Introductionmentioning
confidence: 99%